Tinjauan Literatur: Model dan Mekanisme Distribusi Obat pada Instalasi Farmasi Rumah Sakit di Indonesia: Analisis Kuantitatif Kinerja dan Implikasi Keselamatan Pasien (2015–2025) - Defrika Muharani; Hashifah Faizah; Nailul Fithri Arrasily; Nur Laili Farhiyah; Tri Jenny Minarsih; Budi Hartono; Alfani Ghutsa Daud (SENTRI: Jurnal Riset Ilmiah, 2026)
This literature review aims to synthesize quantitative empirical evidence from studies published between 2015 and 2025 concerning drug distribution models and logistic mechanisms implemented in Hospital Pharmacy Installations in Indonesia. The review focuses on comparing the effectiveness of the Unit Dose Dispensing system with conventional drug distribution models, namely Individual Prescribing and Floor Stock systems, while also examining the role of inventory control methods such as ABC-VEN Analysis and the Economic Order Quantity approach in improving pharmaceutical logistics performance. The findings reveal that national compliance of IFRS with established pharmaceutical care standards remains relatively low, reaching only 65.28%, indicating significant gaps in service quality and operational efficiency. Conventional distribution models are consistently associated with substantial inefficiencies, as reflected by an average inpatient drug return rate of approximately 18%, ranging from 17.11% to 19.62%. Prescription duplication emerges as the dominant contributor, accounting for 42.27% of total medication returns. Conversely, studies evaluating the implementation of the UDD system demonstrate a marked reduction in medication errors, highlighting its effectiveness in enhancing patient safety. From a financial perspective, the application of EOQ-based inventory management has shown the potential to reduce pharmaceutical inventory costs by an average of 8.21% per month, indicating meaningful improvements in cost efficiency. Overall, this review concludes that IFRS in Indonesia must progressively transition toward automated, standardized, and integrated drug distribution systems. Successful implementation requires addressing critical socio-technical challenges, including high initial investment costs, limitations in technological infrastructure, and resistance among healthcare personnel, to achieve optimal patient safety, and service quality.